Effect of the Bio-agents (Bacillus megaterium and Trichoderma album) on Citrus Nematode (Tylenchulus semipenetrans) Infecting Baladi orange and - Elzawahry, Aida M.; Khalil, A. E. M.; Allam, A. D. A.; Mostafa, Radwa G. (Journal of Phytopathology and Disease Management, 2015)
The effect of two commercial compounds namely Bioarc TM (Bacillus megaterium) and Biozeid TM (Trichoderma album) at different rates against Tylenchulus semipenetrans was examined under laboratory and greenhouse conditions. In laboratory experiment, both compounds Bioarc and Biozeid as bio-control agents found to be highly nematostatic agents against J2 of T. semipenetrans. The rates of 20, 25 and 30g/l gave more than 60% J2 mortality after 72h exposure time. The highest effect was achieved at 30 g/l whereas, Bioarc (90.5 %) exhibited the highest effect followed by Biozeid (88.3%) at 30g/l after 72h exposure time. In greenhouse experiment, the bio-agents were evaluated at rates of 20, 25 and 30 g/l compared to nematicide Nemathorin 10% G at recommended dose (12.5 kg/ feddan) on the development of T. semipenetrans infecting Baladi orange and Lime seedlings. Results showed significant differences between the tested rates of both bio-agents. At the higher rate (30.0g/l), Bioarc (89.0, 89.5%; 76.6, 82.9%) was found to be more effective than Biozeid (88.3, 89.0%; 72.0, 77.9%) in reducing number of J2/100g soil and females/g root of Baladi orange and Lime infected with T. semipenetransÂ respectively. Moreover, both Bioarc and Biozeid at 30.0g/l significantly increased plant growth of Baladi orange and Lime infected with T. semipenetrans.